Dietary carotenoids related to risk of incident Alzheimer dementia (AD) and brain AD neuropathology: a community-based cohort of older adults - Yuan, Changzheng; Chen, Hui; Wang, Yamin; Schneider, Julie A; Willett, Walter C; Morris, Martha Clare (The American journal of clinical nutrition, 2021)
Studies have reported a protective relation to cognitive decline with long-term intake of total and individual dietary carotenoids. However, the underlying mechanisms have not yet been clearly established in humans. To evaluate the prospective association between intakes of total and individual carotenoids and risk of incident Alzheimer dementia (AD) and explore the underlying neuropathological basis. Among 927 participants from the Rush Memory and Aging Project who were free from AD at baseline and were followed up for a mean of 7 y, we estimated HRs for AD using Cox proportional hazards models by intakes of energy-adjusted carotenoids. Brain AD neuropathology was assessed in postmortem brain autopsies among 508 deceased participants. We used linear regression to assess the association of carotenoid intake with AD-related neuropathology. Higher intake of total carotenoids was associated with substantially lower hazard of AD after controlling for age, sex, education, ApoE-ε4, participation in cognitively stimulating activities, and physical activity level. Comparing the top and bottom quintiles (median intake: 24.8 compared with 6.7 mg/d) of total carotenoids, the multivariate HR (95% CI) was 0.52 (0.33, 0.81), P-trend < 0.01. A similar association was observed for lutein-zeaxanthin, a weaker linear inverse association was observed for β-carotene, and a marginally significant linear inverse association was found for β-cryptoxanthin. Among the deceased participants, consumers of higher total carotenoids (top compared with bottom tertile, 18.2 compared with 8.2 mg/d) had less global AD pathology (b: -0.10; SE = 0.04; P-trend = 0.01). For individual carotenoids, lutein-zeaxanthin and lycopene were inversely associated with brain global pathology, whereas lutein-zeaxanthin showed additional inverse associations with AD diagnostic score, neuritic plaque severity, and neurofibrillary tangle density and severity. Our findings support a beneficial role of total carotenoid consumption, in particular lutein/zeaxanthin, on AD incidence that may be related to the inhibition of brain β-amyloid deposition and fibril formation.